The Steam Politics of Nanotech: Energy Entanglements in The Diamond Age. Issue 1 (1st April 2023) - Ingwersen, Moritz
Abstract : This article traces the linkage of Victorian energy regimes to nanotechnology in Neal Stephenson's postcyberpunk novel The Diamond Age (1995) to critically examine the unacknowledged cultural entanglements in techno-optimistic visions of post-carbon futures. By invoking the social relations of the steam age as a foil, the novel problematizes the fantasies of control and stability that undergird the history of modern energy imaginaries. Drawing on the novel's incorporation of thermodynamic metaphors, I illustrate how Stephenson's juxtaposition between conservative and entropic systems invites a critique of (petro)modernity that amplifies imaginations of disruption and energy justice.